The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/ecy.3169
|View full text |Cite
|
Sign up to set email alerts
|

Previous exposure mediates the response of eelgrass to future warming via clonal transgenerational plasticity

Abstract: Mortality and shifts in species distributions are among the most obvious consequences of extreme climatic events. However, the sublethal effects of an extreme event can have persistent impacts throughout an individual's lifetime and into future generations via withingeneration and transgenerational phenotypic plasticity. These changes can either confer resilience or increase susceptibility to subsequent stressful events, with impacts on population, community, and potentially ecosystem processes. Here, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 76 publications
3
25
0
Order By: Relevance
“…Here, we showed that elevated temperatures in the fall can intensify the damaging effects of grazing disturbance in the winter. Consistent with previous findings, warming and clipping independently reduced the density and biomass of Zostera assemblages ( warming : DuBois et al., 2020; Kim et al., 2020; Moreno‐Marín et al., 2018; Reynolds et al., 2016; clipping : Hughes, 2006; N.M. Kollars & J.J. Stachowicz, unpubl. data; Ruesink et al., 2012), but these reductions were more severe when the assemblages experienced both disturbance types (Figure 1, Table 1).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Here, we showed that elevated temperatures in the fall can intensify the damaging effects of grazing disturbance in the winter. Consistent with previous findings, warming and clipping independently reduced the density and biomass of Zostera assemblages ( warming : DuBois et al., 2020; Kim et al., 2020; Moreno‐Marín et al., 2018; Reynolds et al., 2016; clipping : Hughes, 2006; N.M. Kollars & J.J. Stachowicz, unpubl. data; Ruesink et al., 2012), but these reductions were more severe when the assemblages experienced both disturbance types (Figure 1, Table 1).…”
Section: Discussionsupporting
confidence: 88%
“…Warming × clipping interaction: F = 3.6, p = 0.07 elevated temperatures in the fall can intensify the damaging effects of grazing disturbance in the winter. Consistent with previous findings, warming and clipping independently reduced the density and biomass of Zostera assemblages (warming: DuBois et al, 2020;Kim et al, 2020;Moreno-Marín et al, 2018;Reynolds et al, 2016;clipping: Hughes, 2006;N.M. Kollars & J.J. Stachowicz, unpubl.…”
Section: F I G U R Esupporting
confidence: 89%
See 3 more Smart Citations